A Comparative Study on Emotional Intelligence among the Executives Working in the Public and Private Commercial Banking Sector of Bangladesh - Uddin, Mohd Kamal; Kabir, Mohammad Jonaed; Taher, Mohammad Abu (Feni University Journal, 2026)
This paper is an initiative to determine the level of emotional intelligence of the workforce, as well as some of the familiar emotional intelligence variables necessary for a balanced emotional state in a demanding workplace like banking and to portray a comparative stature on emotional intelligence level among the executives working in the government owned and private commercial banking sector of Bangladesh. Through random selection, 254 suitable surveys are rounded together for easy processing. This paper follows the "Emotional Competencies Scale" constructed by Dwivedi [1] based on the works of Daniel Goleman [2] to test the same for executives which measures the emotional intelligence competencies that determine the level of emotional intelligence among the respondents. Out of the five variables, the Social skill appears as the most vital as the study finds the highest quantitative figure for eigenvalue (3.4816, and the percentage of variation explained for this variable appears at the highest value of 23.49 and the highest Cronbach Alpha estimates as 0.7894 which indicates that the items comprising the variable go well with superior reliability. This variable is followed by another variable - Self motivation. Considering the summative view on the five different dimensions, the study shows that executives in private commercial banks score higher on Emotional Intelligence Index (EII) above 80%, while at the average EII level (41–60%), executives from both private and stateowned banks demonstrate similar emotional intelligence. FENI UNIVERSITY JOURNAL, 2025, 4(1), PP. (213-236)